1997
DOI: 10.1258/0956462971919877
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycoplasma genitalium in asymptomatic men in Japan

Abstract: We aim to clarify the prevalence of Mycoplasma genitalium in asymptomatic men in Japan. First-catch urine specimens were obtained from 187 asymptomatic Japanese men and examined for the presence of M. genitalium using a polymerase chain reaction (PCR)-based assay. Two (1.1%) of 187 first-catch urine specimens were positive for M. genitalium. The prevalence of M. genitalium in urine specimens of asymptomatic men in Japan is lower than that in asymptomatic men in the UK (6%) and Denmark (9%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
4
5
0
Order By: Relevance
“…Our results are consistent with previous studies that used PCR-based techniques, which have detected this organism in 11%-29% of men with urethritis and in 0%-8.5% of control subjects [6][7][8][9][10][11]26], and in 0.8% of asymptomatic men in Japan recruited from a general medicine clinic [27]. Differences in our study and previous studies include the specimen tested (urine vs. urethra), patient population studied, and the detection techniques for M. genitalium.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with previous studies that used PCR-based techniques, which have detected this organism in 11%-29% of men with urethritis and in 0%-8.5% of control subjects [6][7][8][9][10][11]26], and in 0.8% of asymptomatic men in Japan recruited from a general medicine clinic [27]. Differences in our study and previous studies include the specimen tested (urine vs. urethra), patient population studied, and the detection techniques for M. genitalium.…”
Section: Discussionsupporting
confidence: 91%
“…8 Thus, a prevalence of 2.3% among women in our study is within the expected range as our population consists of a mixture of high and low-risk individuals, as is seen in the descriptive data of the population (table 1). For males, a low prevalence of 1.1% is also in line with other studies showing a prevalence of 1.1% in men attending a Department of Medicine for check-up 27 in Japan and prevalences of 0.8% to 8.5% among asymptomatic men seen in STD clinics. [2][3][4][5][6][7] The low coinfection rate with C trachomatis among both men and women is somewhat surprising, but in line with results found in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Another report showed that 1.1% of asymptomatic Japanese men were positive for M. genitalium. 7 In reports from New Orleans and Denmark, 7% and 9%, respectively, of asymptomatic men were positive for M. genitalium. 8,9 The reasons for the differences in the data between Japan and other countries are not clear.…”
Section: Discussionmentioning
confidence: 98%